The Impact of Trauma from Child Sexual Abuse on Children's Personality Changes - Tsania Salsabila; Elsa Indah Suryani; Baiq Ghefira Rojwani Putri Salsabila; Excell Defry Hardiant (Indonesian Publication Center, 2026)
Children are categorized as a vulnerable population at risk of experiencing violence, with sexual violence being one of its most severe forms. Based on SIMFONI data in 2024, sexual violence is the most common case of violence against children in Indonesia. Sexual violence has the most significant impact on the emotional, mental, and personality development of children in Indonesia. This literature review aims to comprehensively examine sexual violence against children, including definition, resulting personality changes, psychological impacts caused by trauma, contributing factors, pathophysiological aspects, and appropriate intervention strategies for victims. This article was a literature study by examining 22 articles related to child sexual abuse. The findings indicate that sexual violence against children can lead to personality changes through complex neurobiological mechanisms, such as activation of the HPA axis, amygdala dysregulation, and hippocampal dysfunction. Support and intervention for victims of sexual violence involve contributions from the family, community, and the state. These are delivered through emotional support, legal protection, and psychological interventions such as Cognitive Behavioral Therapy (CBT) and Eye Movement Desensitization and Reprocessing (EMDR). Based on these considerations, we are interested in conducting a scientific study on child sexual violence to understand the impact of personality changes in affected children and to evaluate the interventions that can be provided to support the victims’ psychological recovery.